2005
DOI: 10.1053/j.gastro.2005.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Expression Pattern of Wnt Signaling Components in the Adult Intestine

Abstract: Our study predicts a much broader role for Wnt signaling in gut development and homeostasis than was previously anticipated from available genetic studies and identifies novel factors likely involved in promoting canonical and noncanonical Wnt signals in the intestine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
198
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(214 citation statements)
references
References 66 publications
13
198
2
1
Order By: Relevance
“…The localization of both Wnt3 and FZD7 proteins in transformed hepatocytes implies a possible autocrine or paracrine loop of β-catenin activation in HBVrelated HCC. In this regard, a recent study also revealed that both Wnt3 and FZD7 are highly expressed in Paneth cells located in the lower portions of intestinal crypts of the small intestine which is known to be a highly proliferative tissue [47]. Taken together, these findings support the idea that both Wnt3 and FZD7 may be important in cell proliferation and migration via activation of the canonical Wnt signaling cascade.…”
Section: Discussionsupporting
confidence: 64%
“…The localization of both Wnt3 and FZD7 proteins in transformed hepatocytes implies a possible autocrine or paracrine loop of β-catenin activation in HBVrelated HCC. In this regard, a recent study also revealed that both Wnt3 and FZD7 are highly expressed in Paneth cells located in the lower portions of intestinal crypts of the small intestine which is known to be a highly proliferative tissue [47]. Taken together, these findings support the idea that both Wnt3 and FZD7 may be important in cell proliferation and migration via activation of the canonical Wnt signaling cascade.…”
Section: Discussionsupporting
confidence: 64%
“…Finally, to substantiate the responsiveness of these three miRNAs to dnTCF expression, we repeated the dox-dnTCF4 experiment and also included the previously described isogenic DLD1 cell line carrying doxinducible dnTCF1 alleles (van de Wetering et al, 2002) (Supplementary Figure S3). TCF1 and TCF4 have nearly identical binding affinities in vitro, but differ in their regulation-selectivity of specific loci and by their in vivo expression patterns (Waterman, 2004;Gregorieff et al, 2005;Medici et al, 2008). We also included the known growth-suppressive miR-145 and miR-126 miRNAs in the analysis, and found that all five miRNAs were upregulated to varying degrees following dnTCF1/4 expression although miR-30e-3p and miR-574-3p were preferentially regulated by dnTCF4 (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…Sustained activation of the canonical Wnt pathway due to mutational deregulation of Wnt cascade components, such as APC, axin or b-catenin, is associated with several cancers (Lustig and Behrens, 2003;Gregorieff et al, 2005). Moreover, abnormal activation of the Wnt signalling pathway could be independent of Wnt component mutations (Bafico et al, 2004;Merle et al, 2005).…”
Section: Discussionmentioning
confidence: 99%